Advances of mesenchymal stem cells and their derived extracellular vesicles as a promising therapy for acute respiratory distress syndrome: from bench to clinic - Zhuang, Xiaoli; Jiang, Yu; Yang, Xiaofang; Fu, Lin; Luo, Lan; Dong, Ziyuan; Zhao, Ju; Hei, Feilong (Frontiers in Immunology, 2023)
Acute respiratory distress syndrome (ARDS) is an acute inflammatory lung injury characterized by diffuse alveolar damage. The period prevalence of ARDS was 10.4% of ICU admissions in 50 countries. Although great progress has been made in supportive care, the hospital mortality rate of severe ARDS is still up to 46.1%. Moreover, up to now, there is no effective pharmacotherapy for ARDS and most clinical trials focusing on consistently effective drugs have met disappointing results.Mesenchymal stem cells (MSCs) and their derived extracellular vesicles (EVs) have spawned intense interest of a wide range of researchers and clinicians due to their robust anti-inflammatory, antiapoptotic and tissue regeneration properties. A growing body of evidence from preclinical studies confirmed the promising therapeutic potential of MSCs and their EVs in the treatment of ARDS.Based on the inspiring experimental results, clinical trials have been designed to evaluate safety and efficacy of MSCs and their EVs in ARDS patients. Moreover, trials exploring their optimal time window and regimen of drug administration are ongoing. Therefore, this review aims to present an overview of the characteristics of mesenchymal stem cells and their derived EVs, therapeutic mechanisms for ARDS and research progress that has been made over the past 5 years.